An Interview with Dr. Subarna Das Shrestha - Thanju, Jeewan Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
No abstract available DOI: http://dx.doi.org/10.3126/hn.v11i0.7172 Hydro Nepal Vol.11 2011 pp.78-80